Solder paste and solder joint
Patent Information
- Application Number
- JP2021544013
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-09-02
- Filing Date
- 2020-09-02
- Publication Date
- 2025-03-03
- Estimated Expiration
- 2040-09-02
AI Technical Summary
【0017】 本発明に係るはんだペーストは、従来よりも耐熱性、熱伝導性、信頼性の優れたはんだ接合体を形成することができる。
Smart Images

Figure 0007637882000003 
Figure 0007637882000004 
Figure 0007637882000005
Abstract
Description
[Technical field]
[0001] The present invention relates to a solder paste and a solder joint. [Background technology]
[0002] Conventionally, when electronic components such as power conversion elements are fixed to a copper substrate, a method of placing a solder paste or a solder sheet at a required location and heating and soldering the components in a reflow furnace or the like may be adopted. In such a reflow soldering method, the solder melted by heating may be pushed out from between the members to be joined by the weight of the electronic components, etc., resulting in a decrease in the joining strength. In addition, when an electronic component is connected to a wiring substrate by solder bumps, the height of the bumps may become uneven, and the electronic component may be joined to the substrate at an angle. When the electronic component is joined in this way, thermal stress may be applied to the lowered portion of the bump after a long period of use, causing the bumps to crack. In addition to such soldering defects, when the solder joints of electronic components are exposed to high temperatures at high operating temperatures, the solder joints soften (their hardness and strength decrease compared to normal temperature), and the height of the solder joints may change and become uneven due to the weight of the joined components or external forces such as vibration, which may cause joining defects.
[0003] As an improvement measure against these problems, for example, a composite material in which metal particles are dispersed in a solder alloy has been proposed (Patent Documents 1 to 3).
[0004] Patent Document 1 discloses that in a lead-free foam solder mainly composed of Sn, in which high-melting-point metal particles are dispersed in a plate-shaped solder, the metal particles are Ni or Cu, have a melting point of 300°C or more higher than the melting point of the solder alloy, have a particle size of 20 to 300 μm, the variation in particle size of the high-melting-point metal particles is within 40% of the particle size, and an alloy layer between the main component of the solder and the high-melting-point metal particles is formed around the high-melting-point metal particles, and the alloy layer is at least one alloy layer selected from the group consisting of Ni3Sn, Ni3Sn2, and Ni3Sn4 when the metal particles are Ni, and the group consisting of Cu3Sn and Cu6Sn5 when the metal particles are Cu. With this configuration, when a semiconductor element and a substrate are soldered, the semiconductor element is not joined at an angle to the substrate, so there is no decrease in joint strength due to a lack of solder, and the alloy layer with the solder is formed around the metal particles, improving the joint strength between the metal particles and the solder.
[0005] Patent Document 2 describes that in a solder sheet in which metal balls with a higher melting point than the solder constituting the matrix are dispersed, the average diameter of the metal balls is 30 to 300 μm, and the standard deviation of the diameter distribution is 2.0 μm or less. This configuration makes it possible to appropriately maintain the distance (standoff height) between the electrode part of the board and the terminal of the electronic component, and therefore it is said that the thickness of the solder layer that inhibits heat conduction can be suppressed to the greatest extent possible in the region that alleviates the difference in thermal expansion between the board and the electronic component.
[0006] Patent Document 3 discloses a semiconductor device in which a solder layer that bonds chip components and wiring members is sealed with a resin layer, and the solder layer is made of a composite in which a metal powder having a melting point higher than that of the matrix metal is dispersed in a matrix metal. This configuration is said to provide a semiconductor device that can prevent the outflow of the primary mounting solder material and the resulting short circuit, disconnection, and displacement of chip components when a semiconductor device in which chip components as circuit elements are mounted on a substrate and the mounted chip components are sealed with resin is mounted on an external wiring substrate. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] Patent No. 5369682 [Patent Document 2] JP 2005-161338 A [Patent Document 3] International Publication No. 2003 / 021664 Summary of the Invention [Problem to be solved by the invention]
[0008] In recent years, SiC and GaN, which have excellent switching characteristics, have been attracting attention as materials for power semiconductors. For example, power modules using SiC semiconductors can utilize their operating characteristics at high temperatures, so solder alloys that attach power modules to substrates are required to have higher heat resistance, thermal conductivity, and reliability than before. In addition, with the realization of 5th generation communication technology, large amounts of data are exchanged between communication terminals, so solder alloys used in the joints between printed circuit boards and terminals of electronic components of communication terminals are also required to have higher heat resistance, thermal conductivity, and reliability than before.
[0009] The present inventors have conducted extensive research into solder alloys with high heat resistance, thermal conductivity, and reliability, and have found that precipitating an intermetallic compound in a solder alloy is effective in providing such properties (JP Patent Publication 2011-41970). Although such solder alloys meet market demands to a certain extent, there is still room for improvement.
[0010] In the invention described in Patent Document 1, the high melting point metal particles are Ni or Cu, and the alloy layer of the metal particles and Sn, the main component of the solder, is at least one selected from the group consisting of Ni3Sn, Ni3Sn2, Ni3Sn4, or the group consisting of Cu3Sn, Cu6Sn5. However, when the metal particles are Ni, for example, the inventors have found that the wettability with a lead-free solder alloy mainly composed of Sn is low, and the alloy layer may not be formed sufficiently. In addition, when the metal particles are Cu, it has been confirmed that heating causes imbalance in mutual diffusion at the interface between Sn and Cu, resulting in Kirkendall voids, which reduces thermal conductivity and joint strength.
[0011] In the invention described in Patent Document 2, metal balls mainly made of Ni are used as suitable metal balls. However, Patent Document 2 only describes a solder sheet formed by rolling solder strips that have been thinly rolled in advance while inserting metal balls between them, and no intermetallic compounds are present in the obtained solder sheet. Patent Document 2 also only discloses metal balls mainly made of Ni that are formed from pure Ni metal pieces. Furthermore, as described above, Ni metal balls have low wettability with lead-free solder alloys mainly made of Sn, and intermetallic compounds may not be sufficiently formed.
[0012] The invention described in Patent Document 3 describes, as an example, a solder layer composed of a composite in which metal powders formed from various alloys are dispersed in a matrix metal formed from various solder alloys including lead-free solder alloys. However, although Patent Document 3 discloses a paste-like solder material made of a solder alloy and metal powder, it does not pay attention to intermetallic compounds. In addition, the metal powders specified in Patent Document 3 have room for improvement in order to meet the high performance requirements of the market.
[0013] Therefore, an object of the present invention is to provide a solder paste capable of forming a soldered joint including a solder joint having superior heat resistance, thermal conductivity, and reliability compared to conventional solder joints, and to provide a soldered joint having such a solder joint. [Means for solving the problem]
[0014] The present inventors have conducted extensive research to solve the above-mentioned problems, and have found that the above-mentioned problems can be solved by making metal particles of a specific Cu-Ni alloy exist in a lead-free solder alloy mainly composed of Sn, or by making metal particles of a specific Cu-Co alloy exist in a lead-free solder alloy mainly composed of Sn and containing Ni.
[0015] A first aspect of the present invention relates to a solder paste comprising powder of a lead-free solder alloy containing Sn as a main component, and metal particles having a melting point higher than that of the lead-free solder alloy, the metal particles being formed of a Cu-Ni alloy having a Ni content of 0.1 to 90 mass % or a Cu-Co alloy having a Co content of 0.1 to 90 mass %.
[0016] A second aspect of the present invention relates to a solder joint including a solder joint formed using the solder paste, in which (Cu,Ni)6Sn5 or (Cu,Co)6Sn5 is formed at the interface between the metal particles and the solder in the solder joint, or particles in which the alloy forming the metal particles is replaced with (Cu,Ni)6Sn5 or (Cu,Co)6Sn5 are formed. Effect of the Invention
[0017] The solder paste according to the present invention can form a solder joint having better heat resistance, thermal conductivity, and reliability than conventional solder joints. [Brief description of the drawings]
[0018] [Figure 1] 3 is a cross-sectional view in the thickness direction illustrating the structure of a solder joint formed using the solder paste according to the embodiment. FIG. [Diagram 2] 2 is a diagram showing an image of a part of a cross section in the thickness direction of a solder joint of the solder paste obtained in Example 1 observed by SEM. FIG. [Figure 3A]FIG. 13 is a diagram showing an image (5000x) of a part of a cross section in the thickness direction of a soldered joint (observation sample A) including a soldered joint formed using the solder paste obtained in Example 2, observed by SEM. [Figure 3B] FIG. 13 is a diagram showing an image (5000x) of a part of a cross section in the thickness direction of a soldered joint (observation sample B) including a soldered joint formed using the solder paste obtained in Example 2, observed by SEM. [Figure 4A] FIG. 13 is a diagram showing an image (900x) of a part of a cross section in the thickness direction of a soldered joint (observation sample A) including a soldered joint formed using the solder paste obtained in Example 3, observed by SEM. [Figure 4B] FIG. 13 is a diagram showing an image (900x) of a part of a cross section in the thickness direction of a soldered joint (observation sample B) including a soldered joint formed using the solder paste obtained in Example 3, observed by SEM. [Figure 5A] FIG. 4B is a diagram showing an enlarged image (5000x) of a part (within the square frame) of FIG. 4A. [Figure 5B] FIG. 4C is a diagram showing an enlarged image (5000x) of a portion (within the square frame) of FIG. 4B. [Figure 6A] FIG. 13 is a diagram showing an image (900x) of a portion of a cross section in the thickness direction of a soldered joint (observation sample A) including a soldered joint formed using the solder paste obtained in Example 4, observed by SEM. [Figure 6B] FIG. 13 is a diagram showing an image (900x) of a part of a cross section in the thickness direction of a soldered joint (observation sample B) including a soldered joint formed using the solder paste obtained in Example 4, observed by SEM. [Figure 7A] FIG. 6B is a diagram showing an enlarged image (5000x) of a part (within the square frame) of FIG. 6A. [Figure 7B] FIG. 6C is a diagram showing an enlarged image (5000x) of a part (within the square frame) of FIG. 6B. [Figure 8A]FIG. 13 is a diagram showing an image (magnification: 5000) of a part of a cross section in the thickness direction of a soldered joint (observation sample A) including a soldered joint formed using the solder paste obtained in Comparative Example 1, observed by SEM. [Figure 8B] FIG. 13 is a diagram showing an image (magnification: 5000) of a part of a cross section in the thickness direction of a soldered joint (observation sample B) including a soldered joint formed using the solder paste obtained in Comparative Example 1, observed by SEM. [Figure 9A] FIG. 13 is a diagram showing an image (magnification: 5000) of a part of a cross section in the thickness direction of a soldered joint (observation sample A) including a soldered joint formed using the solder paste obtained in Comparative Example 2, observed by SEM. [Figure 9B] FIG. 13 is a diagram showing an image (magnification: 5000) of a part of a cross section in the thickness direction of a soldered joint (observation sample B) including a soldered joint formed using the solder paste obtained in Comparative Example 2, observed by SEM. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0019] The solder paste according to the embodiment of the present invention contains a powder of a lead-free solder alloy (hereinafter, sometimes referred to as a "solder alloy" or a "lead-free solder alloy") whose main component is Sn, and metal particles (hereinafter, sometimes simply referred to as "metal particles") having a melting point higher than that of the solder alloy. The metal particles are formed of a Cu-Ni alloy with a Ni content of 0.1 to 90 mass % or a Cu-Co alloy with a Co content of 0.1 to 90 mass %.
[0020] In this way, by including metal particles formed of a Cu-Ni alloy with a Ni content of 0.1 to 90% by mass or a Cu-Co alloy with a Co content of 0.1 to 90% by mass, (Cu, Ni)6Sn5 or (Cu, Co)6Sn5 can be stably formed at the interface between the metal particles and the solder by heat treatment when forming a solder joint, as an intermetallic compound which is a compound between a lead-free solder alloy mainly composed of Sn and metal particles, or particles in which the alloy forming the metal particles is replaced with (Cu, Ni)6Sn5 or (Cu, Co)6Sn5 can be formed. This is because when the metal particles are formed of a Cu-Ni alloy with a Ni content within a specific range, Sn in the molten solder alloy can be stably diffused into the metal particles compared to the case of Cu or Ni particles, and (Cu, Ni)6Sn5 is stably generated. In addition, even when the metal particles are formed of a Cu-Co alloy with a specific range of Co content, it is believed that the formation of (Cu, Co)6Sn5 is stably performed because Co has properties similar to Ni. Therefore, when the oxide film on the surface of the metal particles is removed by the flux agent contained in the solder paste during heat treatment and the surface comes into contact with the molten solder alloy, (Cu, Ni)6Sn5 or (Cu, Co)6Sn5 is stably formed at the interface between the metal particles and the solder, or particles in which the alloy forming the metal particles is replaced with (Cu, Ni)6Sn5 or (Cu, Co)6Sn5 are formed, depending on various conditions (e.g., heat treatment, composition and size of the metal particles, etc.). In addition, the melting point of (Cu, Ni)6Sn5 is 415°C, and unlike Cu6Sn5, no η-η' phase change occurs at 186°C. When an η-η' phase change occurs, a volume change occurs, which can cause stress concentration in the solder joint and lead to breakage. However, (Cu,Ni)6Sn5 does not cause such a phase change, that is, even if the solder joint is exposed to a high temperature of 186°C or more and then cooled, no phase change occurs, so stress concentration in the solder joint is suppressed. Therefore, from this perspective as well, it is possible to provide a solder joint with good reliability.Since Co has properties similar to Ni, it is believed that (Cu, Co)6Sn5 also suppresses stress concentration in the solder joints, making it possible to provide solder joints with good reliability.
[0021] As described above, metal particles formed of a specific Cu-Ni alloy can stably form (Cu, Ni)6Sn5 at the interface between the metal particles and the solder, or can form particles in which the metal particles are replaced with (Cu, Ni)6Sn5. Metal particles formed of a specific Cu-Co alloy can stably form (Cu, Co)6Sn5 at the interface between the metal particles and the solder. As a result, the properties based on the heat resistance and thermal conductivity of (Cu, Ni)6Sn5 and (Cu, Co)6Sn5 are effectively imparted to the solder joint and, in turn, to the solder joint. In addition, even if repeatedly exposed to high temperatures, it is possible to prevent the generation of Kirkendall voids, as in the case of Cu metal particles. From these results, even if used for a long period of time as a solder joint, damage can be suppressed, and a solder joint with higher reliability than before can be provided. Here, (Cu,Ni)6Sn5 and (Cu,Co)6Sn5 formed at the interface between the metal particles and the solder refer to (Cu,Ni)6Sn5 and (Cu,Co)6Sn5 that are generated between the metal particles and the solder and are in contact with a part or the whole of the surface of the metal particles and are continuous. In addition, when metal particles made of a specific Cu-Co alloy are used, if the solder alloy contains Ni, (Cu,Ni)6Sn5 may also be formed as an intermetallic compound in addition to (Cu,Ni)6Sn5.
[0022] When metal particles formed of a specific Cu-Co alloy are used with a specific lead-free solder alloy powder containing Ni, (Cu, Ni)6Sn5 and (Cu, Co)6Sn5 are generated as intermetallic compounds. As described above, (Cu, Ni, Co)6Sn5 may also be formed. Therefore, as described above, such a solder paste can also provide a solder joint with higher reliability than the conventional solder joint.
[0023] Lead-free solder alloys are alloys mainly composed of Sn. As such lead-free solder alloys, those generally usable in the present technical field can be applied, for example, lead-free solder alloys such as Sn-Ag, Sn-Ag-Cu, Sn-Zn, Sn-Sb, Sn-Ag-Bi, Sn-Ag-In, Sn-Cu-Ni and Sn-Ni. Among them, Sn-Cu-Ni and Sn-Ni lead-free solder alloys are preferred. In addition, Ni, Co, Ge, Ga, Cr, P, Si, Ti, V, Mn, Fe, Zr, Nb, Mo, Pd, Te, Pt, Au, etc. may be appropriately added to such lead-free solder alloys. In addition, when the metal particles are a specific Cu-Co alloy, it may be preferable to use a solder alloy containing Ni from the viewpoint of preventing the elution of Cu in the metal particles and generating (Cu, Ni)6Sn5 to exhibit the above-mentioned functions. In such cases, for example, lead-free solder alloys in which Ni is added to Sn-Cu-Ni and Sn-Ni systems, as well as Sn-Ag, Sn-Ag-Cu, Sn-Zn, Sn-Sb, Sn-Ag-Bi, and Sn-Ag-In systems, can be mentioned. Furthermore, such lead-free solder alloys may be appropriately added with Co, Ge, Ga, Cr, P, Si, Ti, V, Mn, Fe, Zr, Nb, Mo, Pd, Te, Pt, Au, etc.
[0024] The concentration of Sn in the lead-free solder alloy may be any as long as it is the main component, that is, the content thereof may be the highest in the lead-free solder alloy.
[0025] The metal particles are formed of an alloy of Cu and Ni or an alloy of Cu and Co. In the case of an alloy of Cu and Ni, the Ni content in the alloy is 0.1 to 90 mass%, preferably 5 to 45 mass%, more preferably 10 to 40 mass%, and particularly preferably 20 to 35 mass%. In the case of an alloy of Cu and Co, the Co content in the alloy is 0.1 to 90 mass%, preferably 5 to 45 mass%, more preferably 10 to 40 mass%, and particularly preferably 20 to 35 mass%. In the case of a Cu-Ni alloy, the Ni content is within this range, and in the case of a Cu-Co alloy, the Co content is within this range, so that (Cu, Ni)6Sn5 or (Cu, Co)6Sn5 is stably formed at the interface between the metal particles and the solder as an intermetallic compound, which is a compound between the lead-free solder alloy mainly composed of Sn and the metal particles, or particles in which the metal particles are replaced with (Cu, Ni)6Sn5 or (Cu, Co)6Sn5 are formed. As described above, when the metal particles are formed of an alloy of Cu and Co and the solder alloy powder contains Ni, (Cu, Ni)6Sn5 and (Cu, Co)6Sn5 are formed as intermetallic compounds, or (Cu, Ni, Co)6Sn5 can be formed with these.
[0026] When the metal particles are an alloy of Cu and Ni, when the content of Ni in the alloy is 0.1-10 mass%, particularly when it is 2-10 mass%, (Cu, Ni)6Sn5 is easily generated, and the metal particles of the Cu-Ni alloy tend to be easily replaced by (Cu, Ni)6Sn5 particles. In addition, depending on the heating conditions and heating history, when the average particle size of the metal particles is less than 10 μm, the metal particles of the Cu-Ni alloy tend to become (Cu, Ni)6Sn5 particles. These (Cu, Ni)6Sn5 particles have a higher melting point than the solder alloy, have good joint strength with the solder alloy, and can exert the same function as the metal particles of the Cu-Ni alloy and Cu-Co alloy in the solder joint.
[0027] The size of the metal particles may be a size that can be a nucleus for the generation of an intermetallic compound. For example, the average particle diameter may be 5 μm or more. The upper limit of the average particle diameter may be appropriately set according to the size between the parts to be joined, the solder joint strength, the members to be joined, and the like. As described above, when the metal particles are Cu-Ni alloys, and the nuclei of the Cu-Ni alloy are to be left, the average particle diameter may be, for example, 10 μm or more depending on the Ni content. The variation of the particles is not particularly limited, but may be sized as necessary. The shape of the metal particles is not particularly limited, and any shape known in the art may be adopted.
[0028] The content of metal particles in the solder paste is not particularly limited, and can be appropriately determined based on the relationship between the bonding strength and the heat resistance, thermal conductivity, and reliability achieved by the presence of intermetallic compounds, which are required depending on the application.
[0029] Such metal particles can be prepared by a known method, or commercially available ones can be used.
[0030] Solder paste generally contains a flux agent to remove and clean the oxide film on the surfaces of the solder alloy and the parts to be joined, and to enable the joining of the solder and the parts to be joined. The flux agent contains a resin, a solvent, an activator, and a thixotropic agent as its components.
[0031] Examples of the resin include rosins (acid-modified rosin, hydrogenated rosin, disproportionated rosin, polymerized rosin, rosin ester), phenol-modified resins, acrylic resins, etc., and one or a mixture of two or more of the above rosins may be used.
[0032] The solvent is not particularly limited, and those generally used in the present technical field can be applied, for example, alcohols such as ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol monobutyl ether, diethylene glycol monomethyl ether, diethylene glycol monoethyl ether, 2-propanol, decanol, isobornylcyclohexanol (MTPH), octanediol, and 2-hexyl-1-decanol, glycols such as butyl carbitol, dibutyl carbitol, hexylene glycol, hexylene diglycol, and tripropylene glycol monobutyl ether, esters such as butyl benzoate and dibutyl maleate, hydrocarbons such as n-hexane and dodecane, and terpene derivatives such as terpineol, 1,8-terpine monoacetate, and 1,8-terpine diacetate. These solvents may be used alone or in combination.
[0033] The activator is not particularly limited, and those generally used in this technical field can be applied, for example, bisamides such as ethylene bisstearic acid amide, hexamethylene bishydroxystearic acid amide, monoamides such as hydroxystearic acid amide, hydrogenated castor oil, etc. These activators may be contained alone or in combination of two or more kinds.
[0034] In addition to the above-mentioned flux components, the flux agent may contain components that can be added to ordinary solder pastes, such as a viscosity adjuster and an antioxidant.
[0035] The contents of the above-mentioned components contained in the fluxing agent can be appropriately determined.
[0036] A solder joint according to an embodiment of the present invention includes a solder joint formed using the above-mentioned solder paste. An intermetallic compound (Cu, Ni)6Sn5 or (Cu, Co)6Sn5 is formed near the surface of metal particles contained in the solder paste, or particles in which the alloy forming the metal particles is replaced with (Cu, Ni)6Sn5 or (Cu, Co)6Sn5 are formed. Metal particles with such an intermetallic compound formed at the interface with the solder, or particles of an intermetallic compound, can be obtained by wetting a specified metal particle with a molten solder alloy. That is, they are formed when a solder joint is produced using the above-mentioned solder paste.
[0037] The formation of the solder joint can be carried out by a conventional method such as reflow using the above-mentioned solder paste.
[0038] The soldered joint according to the embodiment will be described below with reference to the drawings. FIG. 1 is a cutaway cross-sectional view in the thickness direction for explaining the structure of the soldered joint 10. As shown in FIG. 1, the soldered joint 10 includes a base material A, a base material B, and a solder joint 1 formed between the base materials A and B using a solder paste that is bonded to both of them. The soldered joint 1 in this embodiment is a lead-free solder 2 formed of an alloy mainly composed of Sn, and metal particles 3 formed of (Cu, Ni)6Sn5 (reference number 4) at the interface with the solder are dispersed in the lead-free solder 2. In the embodiment shown in FIG. 1, the metal particles 3 are dispersed in the solder 2. The metal particles 3 formed of (Cu, Ni)6Sn5 (reference number 4) at the interface with the solder are present in close proximity, and the thermal conductivity of (Cu, Ni)6Sn5 (reference number 4) can be more effectively exhibited. Therefore, it is considered that the soldered joint of an electronic component that operates in a high temperature range has excellent heat dissipation characteristics and good heat resistance. In addition, during soldering, due to its thermal conductivity, melting due to heating proceeds instantly throughout the entire solder alloy, which is thought to have the effect of suppressing the retention of voids within the solder alloy bulk. Combined with the property of (Cu, Ni)6Sn5 (symbol 4) that does not undergo η-η' phase change, this is thought to contribute to improving the reliability of the solder joint 10 after cooling.
[0039] Such solder joints have excellent heat resistance, thermal conductivity, and reliability, and are therefore extremely suitable for use as joints in power modules that generate a large amount of heat and are used to control the drive of vehicle motors and other electric motors. EXAMPLES
[0040] The solder paste according to the embodiment of the present invention will be described based on examples.
[0041] Example 1 A solder paste was prepared by mixing 1.2 parts by mass of a solvent (isobornylcyclohexanol), 0.4 parts by mass of adipic acid, 0.8 parts by mass of decanol as fluxing agents, 6.8 parts by mass of a Cu-Ni alloy metal powder with a Ni content of 5.5 atm% (5.1% by mass), and 10.8 parts by mass of a lead-free solder alloy powder mainly composed of Sn (SN100C (registered trademark) manufactured by Nippon Superior Co., Ltd.).
[0042] The obtained solder paste was applied to a ceramic substrate and heated at 300°C for 60 seconds in a nitrogen gas atmosphere to obtain a solder joint formed using the solder paste. The cross section of the obtained solder joint in the thickness direction was confirmed by SEM. As shown in Figure 2, the obtained solder joint was formed using metal particles with a Ni content of 5.1 mass% and a high Cu concentration, but it was confirmed that the metal particles were maintained in the solder alloy. In other words, it is believed that Sn diffused into the metal particles of the Cu-Ni alloy, and (Cu, Ni)6Sn5 was formed at the interface between the metal particles and the solder.
[0043] Example 2 A solder paste was prepared by mixing 1.2 parts by mass of a solvent (isobornylcyclohexanol), 0.4 parts by mass of adipic acid, 0.8 parts by mass of decanol as fluxing agents, 2.0 parts by mass of a Cu-Ni alloy metal powder with a Ni content of 5.1% by mass, and 15.6 parts by mass of a lead-free solder alloy powder mainly composed of Sn (SN100C (registered trademark), manufactured by Nippon Superior Co., Ltd., a Sn-Cu-Ni solder alloy with a composition of 0.7Cu, 0.05Ni, 0.005Ge, balance Sn).
[0044] Example 3 A solder paste was prepared in the same manner as in Example 2, except that a Cu-Ni alloy metal powder containing 30 mass % Ni was used instead of the Cu-Ni alloy metal powder containing 5.1 mass % Ni.
[0045] Example 4 A solder paste was prepared in the same manner as in Example 2, except that a metal powder of a Cu-Co alloy containing 30 mass % of Co was used instead of the metal powder of a Cu-Ni alloy containing 5.1 mass % of Ni.
[0046] Comparative Example 1 A solder paste was prepared in the same manner as in Example 2, except that Cu metal powder was used instead of the Cu-Ni alloy metal powder with an Ni content of 5.1 mass %.
[0047] Comparative Example 2 A solder paste was prepared by mixing 1.2 parts by mass of a solvent (isobornylcyclohexanol), 0.4 parts by mass of adipic acid, 0.8 parts by mass of decanol as fluxing agents, and 17.6 parts by mass of lead-free solder alloy powder containing Sn as the main component (SN100C (registered trademark) manufactured by Nippon Superior Co., Ltd.).
[0048] (evaluation) The solder pastes produced in Examples 2 to 4 and Comparative Examples 1 and 2 were used to carry out the following evaluations.
[0049] <Shear strength test> <<Preparation of measurement samples>> Each solder paste was printed and applied to the mounting portion of the copper foil substrate, which was the base material, and then a resistance component (R2012, length 2 mm, width 1.25 mm) was mounted. This was reflow heated and bonded under conditions of a temperature rise rate of 1.5°C / sec and a maximum temperature of 250°C for 50 seconds, and then cooled and washed with isopropyl alcohol (IPA) to remove the flux, and a soldered joint was obtained in which the copper foil substrate and the resistance component were bonded by a solder joint formed using the solder paste. The obtained soldered joint was used as measurement sample A (initial). A part of measurement sample A was placed in the chamber of a heat cycle tester (manufactured by Espec Corporation, TSA-102EL-A) and subjected to a heat cycle test of 1000 consecutive cycles, in which one cycle was held at -40°C for 30 minutes and then at 125°C for 30 minutes. This was used as measurement sample B (heat cycle).
[0050] <<Measuring share strength>> The measurement samples A and B were set in a shear tester (Shimadzu AG-IS 10kN), and the shear load stress (N) was measured at a shear speed of 0.5mm / min. The maximum value (Max force) of the shear load stress was evaluated as the bonding strength. The maximum value was the average value of the measurements taken 8 times for each sample. In addition, the reduction rate (heat cycle / initial x 100) of each measurement value between the initial and after the heat cycle was calculated to evaluate the influence of the heat cycle. The results are shown in Table 1. As shown in Table 1, the maximum value of each of the examples was larger than that of the comparative example, and the reduction rate exceeded 90%, which was superior to the comparative example, and it can be seen that it is possible to suppress the decrease in bonding strength due to thermal history.
[0051] [Table 1]
[0052] <Measurement of thermal conductivity> <<Preparation of measurement samples>> An appropriate amount of each solder paste was placed on an alumina plate (5 cm long, 5 cm wide, 500 μm thick), and then sandwiched between two alumina plates (5 cm long, 5 cm wide, 500 μm thick) with a spacer of 120 μm thick, and placed on a hot plate. Next, a pressure device was used to apply a load of 0.5 atm from above the alumina plate, while adjusting the temperature of the hot plate to 250 ° C., and after confirming that the solder paste melted and leaked out of the alumina plate, heating was stopped. Next, the plate was cooled using a local blower, and after confirming that the solder solidified, the pressurized state was released. Thereafter, the alumina plate was removed, washed with IPA to remove the flux, and the solder paste was heated and melted to obtain a solder alloy sheet containing metal particles as a measurement sample.
[0053] <<Density measurement>> According to Archimedes' method, each measurement sample was submerged in water in a container with the same inner diameter as the sample, and the sample volume was measured from the change in liquid level before and after the sample was added, and calculated from the sample weight.
[0054] <<Specific heat measurement>> Using a differential scanning calorimeter DSC3500 (manufactured by NETZSCH), the specific heat of each measurement sample was measured by the DSC method under an argon atmosphere at room temperature using sapphire as a reference material.
[0055] <<Measurement of thermal diffusivity>> The thermal diffusivity of each measurement sample, which was blackened using an aerosol dry graphite film forming lubricant DGF (manufactured by Nippon Senpaku Tool Co., Ltd.), was measured in air at room temperature using a laser flash analyzer LFA457 (manufactured by NETZSCH). Each sample was measured using n=4, and the average value was calculated.
[0056] <<Calculation of thermal conductivity>> For each measurement sample, the thermal conductivity was calculated from the density, specific heat, and thermal diffusivity obtained as described above according to the following formula. Thermal Conductivity (W / (m K)) = Thermal Diffusivity (m2 / s)×density(Kg / m 3 ) × specific heat (J / (Kg K))
[0057] The results are shown in Table 2. As shown in Table 2, the thermal conductivity of Examples 2 to 4 is superior to that of Comparative Example 2 in which no metal powder was added, and it is also found that the thermal conductivity is comparable to that of Comparative Example 2 in which copper, which generally has excellent thermal conductivity, was used.
[0058] [Table 2]
[0059] <Observation of the cross-sectional structure of solder joints> <<Preparation of measurement samples>> 0.3 g of each solder paste was applied to the center of copper plate 1 (oxygen-free copper, width 5 mm × length 5 mm × thickness 0.5 mm), and then sandwiched between copper plates 2 (oxygen-free copper, width 5 mm × length 5 mm × thickness 0.5 mm) to prepare a specimen. This was reflow heated at a temperature rise rate of 1.5°C / sec and a maximum temperature of 250°C for 50 seconds, bonded, and then cooled to obtain a soldered joint in which copper plate 1 and copper plate 2 were bonded via a solder joint formed using the solder paste. The obtained soldered joint was used as Sample A for observation. A part of Sample A for observation was placed in an oven (MO-931, manufactured by Toyama Sangyo Co., Ltd.) at 150°C and subjected to an aging test in which it was held for 100 hours. This was used as Sample B for observation (aging). Observation samples A and B were cut in the thickness direction, and the cross sections were polished. The cross sections were then photographed using a scanning electron microscope (JSM-6360LA, manufactured by JEOL Ltd.) (hereinafter, SEM). The images obtained are shown in Figures 3A to 10B. When polishing the cross sections of observation samples A and B, polishing was carried out in stages so that the median value of the added particles could be observed and evaluated, and the point where the diameter was maximum was observed.
[0060] As shown in Fig. 3A to Fig. 7B, in the case of a solder paste containing a predetermined metal particle, (Cu, Ni)6Sn5 or (Cu, Ni)6Sn5 and (Cu, Co)6Sn5 are formed near the surface under general reflow conditions, and when a thermal history is applied, (Cu, Ni)6Sn5 or (Cu, Ni)6Sn5 and (Cu, Co)6Sn5 are further generated near the surface of the metal particle (Examples 3 and 4), or particles of (Cu, Ni)6Sn5 are formed (Example 2). On the other hand, as shown in Fig. 8B, in the case of Comparative Example 2 containing Cu metal particles, the formation of Kirkendall voids is observed when a thermal history is applied. In this way, when metal particles of Cu-Ni alloy or Cu-Co alloy are included, a stable intermetallic compound without Kirkendall voids can be formed, unlike metal particles of Cu alone.
[0061] As described above, the solder joint formed using the solder paste of the embodiment contains predetermined metal particles, which stably forms (Cu, Ni)6Sn5 or (Cu, Ni)6Sn5 and (Cu, Co)6Sn5, thereby suppressing the generation of voids, and even after repeated heat loads, it has excellent shear strength compared to Comparative Example 1 in which Kirkendall voids are generated, and has thermal conductivity comparable to that of the copper metal particles of Comparative Example 1. In addition, by suppressing the generation of voids after repeated heat loads, combined with the properties of (Cu, Ni)6Sn5 and (Cu, Co)6Sn5 that do not cause phase change, it is possible to suppress the concentration of strain stress, which in turn suppresses the starting point of cracks and the deterioration of long-term reliability. [Explanation of symbols]
[0062] 1: solder joint formed using solder paste; 2: lead-free solder; 3: metal particles; 4: (Cu, Ni)6Sn5; 10: solder joint; A, B: substrate
Claims
1. The solder paste contains a powder of a lead-free solder alloy containing Sn as a main component, and metal particles having a melting point higher than that of the lead-free solder alloy, The solder paste, wherein the metal particles are formed of a Cu-Co alloy having a Co content of 0.1 to 90 mass %.
2. A solder joint including a solder joint formed using the solder paste according to claim 1, wherein the solder joint contains (Cu, Co) at the interface between the metal particles and the solder. 6 Sn 5 is formed, or the alloy forming the metal particles is (Cu, Co) 6 Sn 5 A solder joint in which particles are replaced by.
Citation Information
Patent Citations
Apparatus for measuring travelling speed and position of travelling body
JP1978069682A
Joining method by brazing simultaneously with carburization
JP1984076697A
Solder sheet
JP2005161338A
Metal filler, solder paste, and connection structure
JP2014028380A
Semiconductor device, structural body and electronic device
WO2003021664A1